Jørn Utzon's synthesis of Chinese and Japanese architecture in the design for Bagsværd Church. Issue 4 (19th February 2019) - Chiu, Chen-Yu; Goad, Philip; Myers, Peter; Kılınçer, Nur Yıldız
Abstract : In his essay of 1983, 'Towards a Critical Regionalism', Kenneth Frampton referred to the Bagsværd Church as a primary exemplar, briefly citing the architect's representation of 'the Chinese pagoda roof' in this project, to emphasise the importance of crosscultural inspiration in the creation of 'critical regionalism'. Peter Myers followed Frampton in his 1993 'Une histoire inachevée', arguing for the significant role that Chinese architecture played as a source for Utzon's Bagsværd Church design and further variations on the theme of Chinese and Japanese exemplars on Utzon's work follows. Françoise Fromonot established the importance of the 1925 edition of the Yingzao-fashi ( State Building Standard, first published in 1103 ad) and Johannes Prip-Møller's 1937 Chinese Buddhist Monasteries for Utzon; Philip Drew pointed out the significance of the work of Chinese writer Lin Yutang (1895–1976) and historian Osvald Sirén (1879–1966) as important channels through which Utzon perceived East Asian art and architecture; while in 2002, Richard Weston suggested Das Japanische Wohnhaus (1935), written by Japanese architect Tetsuro Yoshida (1894–1956), as a formational influence in Utzon's early perception of Japanese building culture. However, none of these works attempt to clarify the precise role that Chinese and Japanese precedents play in Utzon's architectural career. Two more recent studies, by Philip Goad and Michael Asgaard Andersen, have confirmed the role of Chinese architecture in Utzon's church design and have introduced new evidence and details, but there are still unanswered questions about the exact nature of these influences. This article attempts to address the detailed process of Utzon's cross-cultural practices for his design of the Bagsværd Church in order to reveal how Utzon interpreted specific ideas, ideals, and artefacts from East Asian building culture.